Impact of Linear Operator on the Convergence of HAM Solution: A Modified Operator Approach (Advances in Applied Mathematics and Mechanics, 2018)
The linear operator plays an important role in the computational process ofHomotopy Analysis Method (HAM). In HAM frame any kind of linear operator canbe chosen to develop a solution. Hence, it is easy to introduce the modified/physicalparameter dependent linear operators. The effective use of these operators has beenjudged through solving fluid flow problems. Modification in linear operators affectsthe solution and improves the computational efficiency of HAM for larger values ofparameters. The convergence rate of the solution is rapid and several times higherresulting in less computational time.